Pengaruh Kualitas Sumber Daya Manusia Dan Fasilitas Kerja Terhadap Kinerja Pegawai Pada Balai Uji Terap Teknik Dan Metode Karantina Hewan, Ikan, Dan Tumbuhan - Damayanti, Febiana Nur; Josiah , Trisnowati (Utami Publisher, 2025)
The success of an organization is determined by the performance of its employees. Civil servants are local government officials who assist in the completion of government tasks. The issue that persists to this day is that the resources of government apparatus, both in Ministries/Agencies and Local Governments, have not been fully managed optimally. Therefore, it is not surprising that the management of human resources has become an interesting issue and one of the focal points of the eight programs outlined in the bureaucratic reform roadmap. One of the several mandates that must be carried out within this bureaucratic reform program is the obligation for every government agency to conduct and develop individual employee performance assessments. The task feels very heavy compared to the tasks of addressing the other eight stages in human resource management, such as placement, development, and promotion/termination of employees. The issues at this research include the establishment or determination of appropriate performance indicators for each employee according to their position, performance targets for each employee related to organizational planning, and the means to capture employee performance achievements. The purpose of this research is to determine the influence of the quality of human resources and work facilities on employee performance at the Testing and Implementation Center for Animal, Fish, and Plant Quarantine Techniques and Methods. This research employs a sampling method with a total of 47 respondents. The analysis used is quantitative, and the data processing is conducted using the SPSS program. The results indicate that the quality of human resources has a positive impact on employee performance, with a contribution of 80.8%. Furthermore, work facilities also positively influence employee performance, contributing 76.5%. The regression test shows that there is a positive combined effect of both the quality of human resources and work facilities on employee performance. The influence of the two variables X1 and X2 on Y is 84.4%, while the remaining 15.6% is influenced by other variables outside of this study.